Teachers' Perception of Instructional Technology Application and Integration Competence to the Teaching-Learning Process - Abulencia, Corazon C.; Ampo, Patrick Hamilcar B.; Gonzales, Faye M.; Hyldgaard, Selangan E.; Mangulabnan, Mariver C.; Leva, Erlinda F.; Pizarra, Maria Regina; Victoria, Eric D. S.; Vivo, Ma. Victoria C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Teachers' instructional technology competence is necessary for this information age. With this, teachers need to equip themselves with the knowledge, skills, and competence to apply instructional technologies to deliver the teaching-learning process. This study investigated the teachers’ perception of instructional technology application and integration competence in the teaching-learning process of a selected high school in Candaba, Pampanga, Philippines. This study used descriptive survey research wherein 19 high school teachers participated voluntarily. The researchers also prepared and validated a questionnaire specifically for this study. Data analysis includes the following statistical treatments like frequency, percentage, mean, and Chi-Square. Results of the study showed that the ICT competence of the teachers is on the average level. All the selected teachers integrated technology into teaching. They were highly competent in using MS Word and MS PowerPoint and, on average competent in MS Excel and the Internet. In addition, teachers also encountered problems in using ICT in teaching. Furthermore, teachers perceived that technology in teaching significantly impacts students' learning. It made the students interested and focused, enhanced their teaching activities, and helped them deliver the lesson/s effectively. The study recommended that teachers have training on ICT to equip them with the knowledge and skills to use new programs/applications. The administration should also design a long-term plan for ICT and continue encouraging and training teachers to integrate ICT into teaching.